Musik Edukasi Dan Pentingnya Bagi Sistem Pembelajaran Anak Usia Dini - Saputra, Dadang Wahyu (Institut Agama Islam Negeri Ponorogo, 2024)
This study explains about an educational music or the role of music related to the early childhood education based on using a literature study approach. Music is an art concerning with the combination of vocal or instrumental sounds for the beauty of form or emotional expression, usually according to cultural standards of rhythm, melody, and harmony. Both local songs that are simple in nature and electronic compositions that are more complex are essentially music. In its long history, music has become an integral part of the education. In the realm of education, music is not only an object of study but also a means of learning that can spur and improve the learning outcomes of students. Related to the world of education, in the modern era there has emerged something called educational music which in terms is a type of music used as a learning medium. In various studies it has been proven that using music as a learning medium can stimulate intelligence as well as improve students’ learning results. Therefore, educational music has to be introduced to early childhood education pupils.